Preparation process of mesalazine enteric-coated sustained-release granules
By combining modified starch and chitosan quaternary ammonium salt, mesalazine enteric-coated sustained-release granules were prepared, which solved the problem of the rapid release of mesalazine oral sustained-release granules, achieved the effect of slowly releasing drugs in the intestine and improved the therapeutic effect.
Patent Information
- Application Number
- CN202510405744.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The release rate of mesalamin oral sustained-release particles is too fast, resulting in rapid absorption of the drug in the systemic circulation, reducing the concentration of the intestinal inflammatory sites, thereby weakening the therapeutic effect.
A preparation process is adopted to form hydrophobic starch and chitosan quaternary ammonium modified starch, combined with polyvinyl alcohol and magnesium stearate, ball-like dried pellets covered with mesalazine were prepared, and coated with polyacrylic resin Eudragit s100 to form enteric-coated sustained release particles.
In the acidic environment of the stomach, the coating layer is basically insoluble, and the effective drug release is less than 2%; in the intestine, the drug is released slowly, controlling the release position and rate, improving the therapeutic effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pharmaceutical preparations, in particular to a preparation process of mesalazine enteric-coated sustained-release granules. Background Art
[0002] Mesalazine is a drug for the treatment of ulcerative colitis. Its efficacy on the disease has nothing to do with its concentration in the systemic circulation, but only with the concentration of mesalazine in the intestinal inflammation site. It can achieve better therapeutic effects only when its concentration is maintained at a high level in the intestine, so mesalazine is usually formulated into a colon-targeted dosage form.
[0003] After oral administration of mesalazine sustained-release granules, if the drug is released too quickly, the mesalazine released too quickly will be quickly absorbed by the human body and enter the systemic circulation, thereby reducing its concentration in the intestinal inflammation site and reducing the therapeutic effect. Therefore, it is very necessary to provide a mesalazine enteric-coated sustained-release granule with the function of delaying drug release. Summary of the invention
[0004] The object of the present invention is to provide a preparation process of mesalazine enteric-coated sustained-release granules to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a preparation process of mesalazine enteric-coated sustained-release granules, comprising the following steps: Step 1: Dispersing starch in deionized water, adding sodium hydroxide solution under stirring to obtain a starch dispersion with a pH value of 7.5-8; dispersing octenyl succinic anhydride in anhydrous ethanol to obtain an octenyl succinic anhydride dispersion; adding the octenyl succinic anhydride dispersion to the starch dispersion in three equal additions, controlling the pH value of the system to be maintained at 7.5-8 with sodium hydroxide solution after each addition and reacting for 15-20 minutes; after the reaction is completed, centrifuging the reactant solution, removing the supernatant, washing the precipitate with a citric acid solution with a pH value of 4-4.5 and deionized water, respectively, and vacuum drying to obtain hydrophobic starch; Step 2: Dispersing starch in deionized water to obtain a starch dispersion; adding chitosan quaternary ammonium salt and sodium sulfate, adjusting the pH value to 9-9.5 with a sodium hydroxide solution, adding epichlorohydrin to the reaction system, heating to 40-55° C., reacting for 4-6 hours, adjusting the pH value of the reaction solution to 7.0, cooling, filtering, washing, drying, and crushing to obtain chitosan quaternary ammonium salt modified starch; Step 3: S1: mixing hydrophobic starch, starch and polyvinyl alcohol to obtain a mixture; adding deionized water to the mixture, stirring and gelatinizing at 60-70° C. for 30-40 minutes, and cooling to obtain an adhesive slurry; S2: Mesalazine and chitosan quaternary ammonium salt modified starch are sieved, and the sieved mesalazine and chitosan quaternary ammonium salt modified starch are dispersed in dichloromethane to obtain an oil phase; after stirring for 30-60 minutes, a binder slurry and magnesium stearate are added, and after continuing to stir for 10-20 minutes, polyethylene glycol and silicon dioxide are added and stirred to form a soft material, which is extruded into a strip-shaped soft material by an extrusion spheronizer, and spheronized into spherical wet pills, and the wet pills are vacuum dried at 50-60°C, and sieved to obtain spherical dry pills; S3: Disperse 1.5-2 parts of polyacrylic acid resin Eudragit s100 and 0.1-0.3 parts of ethyl cellulose in a 95% ethanol solution, add 2-2.5 parts of triethyl citrate to prepare a coating solution; after coating the spherical dry pills, vacuum dry them at 40-50°C to obtain mesalazine enteric-coated sustained-release granules.
[0006] Furthermore, in step 1, octenyl succinic anhydride and starch are reacted in a mass ratio of (2-3):100.
[0007] Furthermore, in step 2, the amounts of the components used, by weight, are 6 to 10 parts of starch, 100 parts of deionized water, 0.15 to 0.22 parts of chitosan quaternary ammonium salt, 0.3 to 0.4 parts of sodium sulfate, and 7 to 9 parts of epichlorohydrin.
[0008] Furthermore, in S1, in the mixture, the mass ratio of hydrophobic starch, starch and polyvinyl alcohol is (0.8~1):1:1.
[0009] Furthermore, in S1, the content of each component in the adhesive slurry is, by weight, 10 to 15 parts of the mixture and 100 parts of deionized water.
[0010] Furthermore, in S2, mesalazine and chitosan quaternary ammonium salt modified starch are respectively passed through a 100-150 mesh sieve.
[0011] Furthermore, in S2, the particle size of the spherical wet pellets is 1-1.5 mm.
[0012] Furthermore, in S2, the content of each component in the spherical dry pellets, by weight percentage, is 70-75% mesalamine, 15-20% chitosan quaternary ammonium salt modified starch, 5-10% polyethylene glycol, 1-5% silicon dioxide, and 1-5% magnesium stearate.
[0013] Furthermore, in S3, in the coating solution, the mass ratio of polyacrylic acid resin Eudragit s100, ethyl cellulose, and triethyl citrate is (1.5~2):(0.1~0.3):(2~2.5).
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a preparation process of mesalazine enteric-coated sustained-release granules. The coating layer of the sustained-release granules is affected by the pH value of the environmental medium, is basically insoluble in the acidic environment of the stomach, and the release amount of the effective drug is less than 2%, while the drug can be continuously and slowly released in the intestine, thereby controlling the release position and release rate of the drug.
[0015] In the present invention, the inventors adopt two methods to modify starch respectively. Chitosan quaternary ammonium salt is used to modify starch. Chitosan quaternary ammonium salt is grafted onto starch particles through chemical bonds, cross-linked to form a three-dimensional network structure, and "pits" are formed on the surface of starch particles, thereby increasing the specific surface area of starch and improving the adsorption amount of mesalazine. At the same time, the modified starch also has a certain emulsification effect in the emulsion, so the stability of the emulsion is higher.
[0016] Octenyl succinic anhydride is also used in the present invention to modify starch to obtain hydrophobic starch. Hydrophobic starch is mixed with starch and polyvinyl alcohol to prepare adhesive slurry, and adhesive can form a close combination between the starch particles of the loaded drug, and enhance the agglomeration of the particles. The adhesive adding hydrophobic starch can reduce the viscosity of the slurry on the one hand, and conveniently extrusion molding is performed when preparing soft materials, and soft materials are prevented from adhering to the equipment, and the problems such as soft materials hanging on the wall and uneven molding are prevented, and the hydrophobic segment and the remaining hydrophilic segment can improve the stability of the emulsion after adding, and improve the bonding efficiency between particles. In addition, when adding adhesive slurry, it is necessary to first add adhesive and magnesium stearate, and then add other auxiliary agents after a period of time, so as to avoid the auxiliary agent particles being dispersed in the middle of the starch particles of the loaded drug, avoid uneven drug concentration in the prepared particles, and improve the overall stability of the sustained-release granule drug effect. DETAILED DESCRIPTION
[0017] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0018] Materials and sources used in the present invention: polyacrylic acid resin Eudragit s100 comes from Shanghai Changwei Pharmaceutical Excipients Technology Co., Ltd.; starch is edible corn starch, which comes from Shandong Shouguang Juneng Golden Corn Development Co., Ltd.; chitosan quaternary ammonium salt comes from Hubei Changao Pharmaceutical Co., Ltd., food grade; ethyl cellulose comes from Hubei Nona Technology Co., Ltd., pharmaceutical grade.
[0019] Example 1: A process for preparing mesalazine enteric-coated sustained-release granules, comprising the following steps: Step 1: Disperse starch in deionized water, add sodium hydroxide solution under stirring to obtain a starch dispersion with a pH value of 7.5; disperse octenyl succinic anhydride in anhydrous ethanol to obtain an octenyl succinic anhydride dispersion; add the octenyl succinic anhydride dispersion to the starch dispersion in three equal portions, and control the pH value of the system to be maintained at 7.5 with sodium hydroxide solution after each addition and react for 15 minutes; after the reaction is completed, centrifuge the reactant solution, remove the supernatant, wash the precipitate with a citric acid solution with a pH value of 4 and deionized water, respectively, and vacuum dry to obtain hydrophobic starch; wherein, the octenyl succinic anhydride and the starch are reacted at a mass ratio of 3:100; Step 2: 8 g of starch was dispersed in 100 g of deionized water to obtain a starch dispersion; 0.2 g of chitosan quaternary ammonium salt and 0.35 g of sodium sulfate were added, the pH value was adjusted to 9 with a sodium hydroxide solution, 7 g of epichlorohydrin was added to the reaction system, the temperature was raised to 45° C., the reaction was carried out for 4 hours, the pH value of the reaction solution was adjusted to 7.0, the reaction solution was cooled, filtered, washed, dried, and crushed to obtain chitosan quaternary ammonium salt modified starch; Step 3: S1: Mix hydrophobic starch, starch and polyvinyl alcohol in a mass ratio of 1:1:1 to obtain a mixture, add 100 g of deionized water to 13 g of the mixture, stir and gelatinize at 60° C. for 30 min, and cool to obtain an adhesive slurry; S2: Mesalazine and chitosan quaternary ammonium salt modified starch are respectively passed through a 100-mesh sieve, and the sieved mesalazine and chitosan quaternary ammonium salt modified starch are dispersed in dichloromethane to obtain an oil phase; after stirring for 30 minutes, a binder slurry and magnesium stearate are added, and after continuing to stir for 10 minutes, polyethylene glycol and silicon dioxide are added and stirred to form a soft material, which is extruded into a strip-shaped soft material using an extrusion spheronizer, and spheronized into spherical wet pills with a particle size of 1 mm, and the wet pills are vacuum dried at 50° C. and sieved to obtain spherical dry pills; the content of each component in the spherical dry pills is, by weight percentage, 70% mesalazine, 20% chitosan quaternary ammonium salt modified starch, 8% polyethylene glycol, 1% silicon dioxide, and 1% magnesium stearate; S3: 1.8 g of polyacrylic acid resin Eudragit s100 and 0.2 g of ethyl cellulose were dispersed in a 95% ethanol solution, and 2 g of triethyl citrate was added to prepare a coating solution; after coating the spherical dry pellets, they were vacuum dried at 40°C to obtain mesalazine enteric-coated sustained-release granules.
[0020] Embodiment 2: A preparation process of mesalazine enteric-coated sustained-release granules, comprising the following steps: Step 1: Disperse starch in deionized water, add sodium hydroxide solution under stirring to obtain a starch dispersion with a pH value of 7.8; disperse octenyl succinic anhydride in anhydrous ethanol to obtain an octenyl succinic anhydride dispersion; add the octenyl succinic anhydride dispersion to the starch dispersion in three equal portions, and control the pH value of the system to be maintained at 7.5 with sodium hydroxide solution after each addition and react for 18 minutes; after the reaction is completed, centrifuge the reactant solution, remove the supernatant, wash the precipitate with a citric acid solution with a pH value of 4.3 and deionized water, respectively, and vacuum dry to obtain hydrophobic starch; wherein, the octenyl succinic anhydride and the starch are reacted at a mass ratio of 3:100; Step 2: 8 g of starch was dispersed in 100 g of deionized water to obtain a starch dispersion; 0.2 g of chitosan quaternary ammonium salt and 0.35 g of sodium sulfate were added, the pH value was adjusted to 9.3 with a sodium hydroxide solution, 7 g of epichlorohydrin was added to the reaction system, the temperature was raised to 40° C., the reaction was carried out for 5 h, the pH value of the reaction solution was adjusted to 7.0, the reaction solution was cooled, filtered, washed, dried, and crushed to obtain chitosan quaternary ammonium salt modified starch; Step 3: S1: Mix hydrophobic starch, starch and polyvinyl alcohol in a mass ratio of 1:1:1 to obtain a mixture, add 100 g of deionized water to 13 g of the mixture, stir and gelatinize at 65° C. for 35 min, and cool to obtain an adhesive slurry; S2: Mesalazine and chitosan quaternary ammonium salt modified starch are respectively passed through a 120-mesh sieve, and the sieved mesalazine and chitosan quaternary ammonium salt modified starch are dispersed in dichloromethane to obtain an oil phase; after stirring for 45 minutes, a binder slurry and magnesium stearate are added, and after continuing to stir for 15 minutes, polyethylene glycol and silicon dioxide are added and stirred to form a soft material, which is extruded into a strip-shaped soft material using an extrusion spheronizer, and spheronized into spherical wet pills with a particle size of 1.2 mm, and the wet pills are vacuum dried at 55° C. and sieved to obtain spherical dry pills; the content of each component in the spherical dry pills, by weight percentage, is 70% mesalazine, 20% chitosan quaternary ammonium salt modified starch, 8% polyethylene glycol, 1% silicon dioxide, and 1% magnesium stearate; S3: 1.8 g of polyacrylic acid resin Eudragit s100 and 0.2 g of ethyl cellulose were dispersed in a 95% ethanol solution, and 2 g of triethyl citrate was added to prepare a coating solution; after coating the spherical dry pills, they were vacuum dried at 45°C to obtain mesalazine enteric-coated sustained-release granules.
[0021] Example 3: A process for preparing mesalazine enteric-coated sustained-release granules, comprising the following steps: Step 1: Disperse starch in deionized water, add sodium hydroxide solution under stirring to obtain a starch dispersion with a pH value of 8; disperse octenyl succinic anhydride in anhydrous ethanol to obtain an octenyl succinic anhydride dispersion; add the octenyl succinic anhydride dispersion to the starch dispersion in three equal portions, and control the pH value of the system to be maintained at 8 with sodium hydroxide solution after each addition and react for 20 minutes; after the reaction is completed, centrifuge the reactant solution, remove the supernatant, wash the precipitate with a citric acid solution with a pH value of 4.5 and deionized water, respectively, and vacuum dry to obtain hydrophobic starch; wherein, the octenyl succinic anhydride and the starch are reacted at a mass ratio of 3:100; Step 2: 8 g of starch was dispersed in 100 g of deionized water to obtain a starch dispersion; 0.2 g of chitosan quaternary ammonium salt and 0.35 g of sodium sulfate were added, the pH value was adjusted to 9.5 with a sodium hydroxide solution, 7 g of epichlorohydrin was added to the reaction system, the temperature was raised to 55° C., the reaction was carried out for 6 h, the pH value of the reaction solution was adjusted to 7.0, the reaction solution was cooled, filtered, washed, dried, and crushed to obtain chitosan quaternary ammonium salt modified starch; Step 3: S1: Mix hydrophobic starch, starch and polyvinyl alcohol in a mass ratio of 1:1:1 to obtain a mixture, add 100 g of deionized water to 13 g of the mixture, stir and gelatinize at 65° C. for 35 min, and cool to obtain an adhesive slurry; S2: Mesalazine and chitosan quaternary ammonium salt modified starch are respectively passed through a 150-mesh sieve, and the sieved mesalazine and chitosan quaternary ammonium salt modified starch are dispersed in dichloromethane to obtain an oil phase; after stirring for 45 minutes, a binder slurry and magnesium stearate are added, and after continuing to stir for 15 minutes, polyethylene glycol and silicon dioxide are added and stirred to form a soft material, which is extruded into a strip-shaped soft material using an extrusion spheronizer, and spheronized into spherical wet pellets with a particle size of 1.2 mm, and the wet pellets are vacuum dried at 60° C. and sieved to obtain spherical dry pellets; the content of each component in the spherical dry pellets, by weight percentage, is 70% mesalazine, 20% chitosan quaternary ammonium salt modified starch, 8% polyethylene glycol, 1% silicon dioxide, and 1% magnesium stearate; S3: 1.8 g of polyacrylic acid resin Eudragit s100 and 0.2 g of ethyl cellulose were dispersed in a 95% ethanol solution, and 2 g of triethyl citrate was added to prepare a coating solution; after coating the spherical dry pellets, vacuum drying was performed at 50°C to obtain mesalazine enteric-coated sustained-release granules.
[0022] Comparative Example 1: No hydrophobic starch was added to the adhesive slurry, and the other parameters were the same as those in Example 1.
[0023] Step 1: 8 g of starch was dispersed in 100 g of deionized water to obtain a starch dispersion; 0.2 g of chitosan quaternary ammonium salt and 0.35 g of sodium sulfate were added, the pH value was adjusted to 9 with a sodium hydroxide solution, 7 g of epichlorohydrin was added to the reaction system, the temperature was raised to 45° C., the reaction was carried out for 4 hours, the pH value of the reaction solution was adjusted to 7.0, the reaction solution was cooled, filtered, washed, dried, and crushed to obtain chitosan quaternary ammonium salt modified starch; Step 2: S1: starch and polyvinyl alcohol were mixed in a mass ratio of 1:1 to obtain a mixture, 100 g of deionized water was added to 13 g of the mixture, the mixture was stirred for gelatinization at 60° C. for 30 min, and the temperature was lowered to obtain an adhesive slurry; S2: Mesalazine and chitosan quaternary ammonium salt modified starch are respectively passed through a 100-mesh sieve, and the sieved mesalazine and chitosan quaternary ammonium salt modified starch are dispersed in dichloromethane to obtain an oil phase; after stirring for 30 minutes, a binder slurry and magnesium stearate are added, and after continuing to stir for 10 minutes, polyethylene glycol and silicon dioxide are added and stirred to form a soft material, which is extruded into a strip-shaped soft material using an extrusion spheronizer, and spheronized into spherical wet pills with a particle size of 1 mm, and the wet pills are vacuum dried at 50° C. and sieved to obtain spherical dry pills; the content of each component in the spherical dry pills is, by weight percentage, 70% mesalazine, 20% chitosan quaternary ammonium salt modified starch, 8% polyethylene glycol, 1% silicon dioxide, and 1% magnesium stearate; S3: 1.8 g of polyacrylic acid resin Eudragit s100 and 0.2 g of ethyl cellulose were dispersed in a 95% ethanol solution, and 2 g of triethyl citrate was added to prepare a coating solution; after coating the spherical dry pellets, they were vacuum dried at 40°C to obtain mesalazine enteric-coated sustained-release granules.
[0024] Comparative Example 2: Microcrystalline cellulose was used instead of chitosan quaternary ammonium salt modified starch, and the other parameters were the same as those in Example 2.
[0025] Step 1: Disperse starch in deionized water, add sodium hydroxide solution under stirring to obtain a starch dispersion with a pH value of 7.8; disperse octenyl succinic anhydride in anhydrous ethanol to obtain an octenyl succinic anhydride dispersion; add the octenyl succinic anhydride dispersion to the starch dispersion in three equal portions, and control the pH value of the system to be maintained at 7.5 with sodium hydroxide solution after each addition and react for 18 minutes; after the reaction is completed, centrifuge the reactant solution, remove the supernatant, wash the precipitate with a citric acid solution with a pH value of 4.3 and deionized water, respectively, and vacuum dry to obtain hydrophobic starch; wherein, the octenyl succinic anhydride and the starch are reacted at a mass ratio of 3:100; Step 2: S1: Mix hydrophobic starch, starch and polyvinyl alcohol in a mass ratio of 1:1:1 to obtain a mixture, add 100 g of deionized water to 13 g of the mixture, stir and gelatinize at 65° C. for 35 min, and cool to obtain an adhesive slurry; S2: Mesalazine and microcrystalline cellulose are respectively sieved with 120 meshes, and the sieved mesalazine and microcrystalline cellulose are dispersed in dichloromethane to obtain an oil phase; after stirring for 45 minutes, a binder slurry and magnesium stearate are added, and after continuing to stir for 15 minutes, polyethylene glycol and silicon dioxide are added and stirred to form a soft material, which is extruded into a strip-shaped soft material using an extrusion spheronizer, and spheronized into spherical wet pills with a particle size of 1.2 mm, and the wet pills are vacuum dried at 55° C. and sieved to obtain spherical dry pills; the content of each component in the spherical dry pills, by weight percentage, is 70% mesalazine, 20% microcrystalline cellulose, 8% polyethylene glycol, 1% silicon dioxide, and 1% magnesium stearate; S3: 1.8 g of polyacrylic acid resin Eudragit s100 and 0.2 g of ethyl cellulose were dispersed in a 95% ethanol solution, and 2 g of triethyl citrate was added to prepare a coating solution; after coating the spherical dry pills, they were vacuum dried at 45°C to obtain mesalazine enteric-coated sustained-release granules.
[0026] Comparative Example 3: The adhesive slurry, magnesium stearate, polyethylene glycol and silicon dioxide were added simultaneously to prepare a soft material.
[0027] Step 1: Disperse starch in deionized water, add sodium hydroxide solution under stirring to obtain a starch dispersion with a pH value of 8; disperse octenyl succinic anhydride in anhydrous ethanol to obtain an octenyl succinic anhydride dispersion; add the octenyl succinic anhydride dispersion to the starch dispersion in three equal portions, and control the pH value of the system to be maintained at 8 with sodium hydroxide solution after each addition and react for 20 minutes; after the reaction is completed, centrifuge the reactant solution, remove the supernatant, wash the precipitate with a citric acid solution with a pH value of 4.5 and deionized water, respectively, and vacuum dry to obtain hydrophobic starch; wherein, the octenyl succinic anhydride and the starch are reacted at a mass ratio of 3:100; Step 2: 8 g of starch was dispersed in 100 g of deionized water to obtain a starch dispersion; 0.2 g of chitosan quaternary ammonium salt and 0.35 g of sodium sulfate were added, the pH value was adjusted to 9.5 with a sodium hydroxide solution, 7 g of epichlorohydrin was added to the reaction system, the temperature was raised to 55° C., the reaction was carried out for 6 h, the pH value of the reaction solution was adjusted to 7.0, the reaction solution was cooled, filtered, washed, dried, and crushed to obtain chitosan quaternary ammonium salt modified starch; Step 3: S1: Mix hydrophobic starch, starch and polyvinyl alcohol in a mass ratio of 1:1:1 to obtain a mixture, add 100 g of deionized water to 13 g of the mixture, stir and gelatinize at 65° C. for 35 min, and cool to obtain an adhesive slurry; S2: Mesalazine and chitosan quaternary ammonium salt modified starch are respectively passed through a 150-mesh sieve, and the sieved mesalazine and chitosan quaternary ammonium salt modified starch are dispersed in dichloromethane to obtain an oil phase; after stirring for 45 minutes, a binder slurry, magnesium stearate, polyethylene glycol, and silicon dioxide are added and stirred to form a soft material, which is extruded into a strip-shaped soft material using an extrusion spheronizer, and spheronized into spherical wet pellets with a particle size of 1.2 mm, and the wet pellets are vacuum dried at 60° C. and sieved to obtain spherical dry pellets; the content of each component in the spherical dry pellets, by weight percentage, is 70% mesalazine, 20% chitosan quaternary ammonium salt modified starch, 8% polyethylene glycol, 1% silicon dioxide, and 1% magnesium stearate; S3: 1.8 g of polyacrylic acid resin Eudragit s100 and 0.2 g of ethyl cellulose were dispersed in a 95% ethanol solution, and 2 g of triethyl citrate was added to prepare a coating solution; after coating the spherical dry pellets, vacuum drying was performed at 50°C to obtain mesalazine enteric-coated sustained-release granules.
[0028] Experiment: The mesalazine enteric-coated sustained-release granules prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested.
[0029] Drug loading: The samples were dispersed in 10 mL of anhydrous ethanol and fully expanded at 37°C for 24 hours; the expanded samples were crushed and centrifuged at 15,000 rpm, the supernatant was collected, and 5-aminosalicylic acid was detected by HPLC. Drug loading rate (%) = amount of 5-aminosalicylic acid / amount of mesalamine sustained-release granules × 100%.
[0030] Sustained release: The release was determined by using the first method of the dissolution method (Appendix XC of Part II of the 2010 edition of the Chinese Pharmacopoeia, Method I, basket method), with 900 mL of 0.1 mol / L HCl and phosphate buffer with a pH value of 6.8 as release media, respectively, to simulate the human gastrointestinal tract for pH medium change to determine the release; the sample was first placed in 0.1 mol / L HCl for 2 h, with a rotation speed of 100 rpm and a temperature of 37 ° C, and then replaced with phosphate buffer with a pH value of 6.8 for 3 h, and the medium change was completed within 5 min; the sample was taken once every 15 min, and an equal amount of isothermal medium was supplemented at the same time, filtered with a 0.45 μm microporous membrane, and an appropriate amount of the filtrate was taken. After dilution, the absorbance was determined according to the UV-Vis spectrophotometry (Appendix IVA of Part II of the 2010 edition of the Chinese Pharmacopoeia), and the release was calculated; the experimental results are shown in Table 1.
[0031] Table 1. Performance test results of mesalazine enteric-coated sustained-release granules
[0032] Conclusion: The data of Examples 1 to 3 show that the sustained-release granules prepared by the present invention have good performance, with a 2h release amount of less than 2% in a medium simulating a gastric environment, and a 3h release amount of about 50% in a medium simulating an intestinal environment, which can achieve precise drug delivery. The data of Example 1 and Comparative Example 1 show that after adding hydrophobic starch, the release time of the sustained-release granules in the intestinal environment is longer. The data of Example 2 and Comparative Example 2 show that more effective ingredients can be loaded by using chitosan quaternary ammonium salt modified starch as a carrier. The data of Example 3 and Comparative Example 3 show that after the adhesive slurry, magnesium stearate and other additives are directly blended to prepare a soft material, the drug loading is reduced and the sustained-release effect is poor.
[0033] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process of mesalazine enteric-coated sustained-release granules, characterized in that: The following steps are involved: Step 1: Dispersing starch in deionized water, adding sodium hydroxide solution under stirring to obtain a starch dispersion with a pH value of 7.5-8; dispersing octenyl succinic anhydride in anhydrous ethanol to obtain an octenyl succinic anhydride dispersion; adding the octenyl succinic anhydride dispersion to the starch dispersion in three equal additions, controlling the pH value of the system to be maintained at 7.5-8 with sodium hydroxide solution after each addition and reacting for 15-20 minutes; after the reaction is completed, centrifuging the reactant solution, removing the supernatant, washing the precipitate with a citric acid solution with a pH value of 4-4.5 and deionized water, respectively, and vacuum drying to obtain hydrophobic starch; Step 2: Dispersing starch in deionized water to obtain a starch dispersion; adding chitosan quaternary ammonium salt and sodium sulfate, adjusting the pH value to 9-9.5 with a sodium hydroxide solution, adding epichlorohydrin to the reaction system, heating to 40-55° C., reacting for 4-6 hours, adjusting the pH value of the reaction solution to 7.0, cooling, filtering, washing, drying, and crushing to obtain chitosan quaternary ammonium salt modified starch; Step 3: S1: mixing hydrophobic starch, starch and polyvinyl alcohol to obtain a mixture; adding deionized water to the mixture, stirring and gelatinizing at 60-70° C. for 30-40 minutes, and cooling to obtain an adhesive slurry; S2: Mesalazine and chitosan quaternary ammonium salt modified starch are sieved, and the sieved mesalazine and chitosan quaternary ammonium salt modified starch are dispersed in dichloromethane to obtain an oil phase; after stirring for 30-60 minutes, a binder slurry and magnesium stearate are added, and after continuing to stir for 10-20 minutes, polyethylene glycol and silicon dioxide are added and stirred to form a soft material, which is extruded into a strip-shaped soft material by an extrusion spheronizer, and spheronized into spherical wet pills, and the wet pills are vacuum dried at 50-60°C, and sieved to obtain spherical dry pills; S3: Disperse 1.5-2 parts of polyacrylic acid resin Eudragit s100 and 0.1-0.3 parts of ethyl cellulose in a 95% ethanol solution, add 2-2.5 parts of triethyl citrate to prepare a coating solution; after coating the spherical dry pills, vacuum dry them at 40-50°C to obtain mesalazine enteric-coated sustained-release granules.
2. The preparation process of mesalazine enteric-coated sustained-release granules according to claim 1, characterized in that: In step 1, octenyl succinic anhydride and starch are reacted in a mass ratio of (2-3):
100.
3. The preparation process of mesalazine enteric-coated sustained-release granules according to claim 1, characterized in that: In step 2, the amount of each component used, by weight, is 6 to 10 parts of starch, 100 parts of deionized water, 0.15 to 0.22 parts of chitosan quaternary ammonium salt, 0.3 to 0.4 parts of sodium sulfate, and 7 to 9 parts of epichlorohydrin.
4. The preparation process of mesalazine enteric-coated sustained-release granules according to claim 1, characterized in that: In S1, in the mixture, the mass ratio of hydrophobic starch, starch and polyvinyl alcohol is (0.8~1):1:
1.
5. The preparation process of mesalazine enteric-coated sustained-release granules according to claim 1, characterized in that: In S1, the content of each component in the adhesive slurry is, by weight, 10 to 15 parts of the mixture and 100 parts of deionized water.
6. The preparation process of mesalazine enteric-coated sustained-release granules according to claim 1, characterized in that: In S2, mesalazine and chitosan quaternary ammonium salt modified starch are respectively passed through 100-150 mesh sieves.
7. The preparation process of mesalazine enteric-coated sustained-release granules according to claim 1, characterized in that: In S2, the particle size of the spherical wet pellets is 1~1.5mm.
8. The preparation process of mesalazine enteric-coated sustained-release granules according to claim 1, characterized in that: In S2, the content of each component in the spherical dry pellets, by weight percentage, is 70-75% mesalamine, 15-20% chitosan quaternary ammonium salt modified starch, 5-10% polyethylene glycol, 1-5% silicon dioxide, and 1-5% magnesium stearate.
9. The preparation process of mesalazine enteric-coated sustained-release granules according to claim 1, characterized in that: In S3, in the coating solution, the mass ratio of polyacrylic acid resin Eudragit s100, ethyl cellulose, and triethyl citrate is (1.5~2):(0.1~0.3):(2~2.5).
10. Mesalazine enteric-coated sustained-release granules prepared according to the preparation process of any one of claims 1 to 9.
Citation Information
Patent Citations
Mesalazine sustained-release pellets, preparation method thereof and mesalazine sustained-release capsule
CN105456223A
Oxiracetam enteric-coated preparation and preparation method thereof
CN109718222A
Mesalazine sustained-release preparation with high drug loading and preparation method thereof
CN112891321A
Process for producing starch octenylsucciniate
CN1962696A
Delayed release pharmaceutical composition of mesalamine
US20120282333A1